Antitubercular activity of Ru (II) isoniazid complexes - Aguiar, Inara de; Tavares, Aline; Roveda, Antonio C.; Silva, Augusto C. H. da; Marino, Leonardo B. [UNESP]; Lopes, Erica O. [UNESP]; Pavan, Fernando R. [UNESP]; Lopes, Luiz G. F.; Franco, Douglas W. (Elsevier B.V., 2015)
Despite the resistance developed by the Mycobacterium tuberculosis (MTb) strains, isoniazid (INK) has been recognized as one of the best drug for treatment of Tuberculosis (Tb). The coordination of INH to ruthenium metal centers was investigated as a strategy to enhance the activity of this drug against the sensitive and resistant strains of MTb. The complexes trans-[Ru(NH3)(4)(L)(INH)](2+) (L = SO2 or NH3) were isolated and their chemical and antituberculosis properties studied. The minimal inhibitory concentration (MIC) data show that [Ru(NH3)(5)(INH)](2+) was active in both resistant and sensitive strains, whereas free INK (non-coordinated) showed to be active only against the sensitive strain. The coordination of INH to the metal center in both [Ru(NH3)(5)(INH)](2+) and trans-[Ru(NH3)(4)(SO2)(INH)](2+) complexes led to a shift in the INH oxidation potential to less positive values compared to free INH. Despite, the ease of oxidation of INH did not lead to an increase in the in vitro INH activity against MTb, it might have provided sensitivity toward resistant strains. Furthermore, ruthenium complexes with chemical structures analogous to those described above were synthesized using the oxidation products of INK as ligands (namely, isonicotinic acid and isonicotinamide). These last compounds were not active against any strains of MTb. Moreover, according to DFT calculations the formation of the acyl radical, a proposed intermediate in the INH oxidation, is favored in the [Ru(NH3)(5)(INH)](2+) complex by 50.7 kcal mol(-1) with respect to the free INH. This result suggests that the stabilization of the acyl radical promoted by the metal center would be a more important feature than the oxidation potential of the INH for the antituberculosis activity against resistant strains. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Tuberculosis; Resistant strains; Metal complexes; Metallodrugs; Tetraammine- and pentaammine ruthenium complexes; Isoniazid